Fashion, Difference and Identity in Serbian Socialism - Ildiko Erdei (Etnoantropološki Problemi, 2008)
On the occasion of publishing Danijela Velimirović, Aleksandar Joksimović. Moda i identitet. Utopija. Beograd 2008